Preparing for the future: teaching scenario planning at the graduate level. Issue 5 (22nd May 2009) - Biggs, Reinette; Diebel, Matthew W; Gilroy, David; Kamarainen, Amy M; Kornis, Matthew S; Preston, Nicholas D; Schmitz, Jennifer E; Uejio, Christopher K; Van De Bogert, Matthew C; Weidel, Brian C; West, Paul C; Zaks, David PM; et al.
Abstract : Are environmental science students developing the mindsets and obtaining the tools needed to help address the considerable challenges posed by the 21st century? Today's major environmental issues are characterized by high‐stakes decisions and high levels of uncertainty. Although traditional scientific approaches are valuable, contemporary environmental issues also require new tools and new ways of thinking. We provide an example of how such new, or "post‐normal", approaches have been taught at the graduate level, through practical application of scenario planning. Surveyed students reported that they found the scenario planning course highly stimulating, thought‐provoking, and inspiring. Key learning points included recognizing the need for multiple points of view when considering complex environmental issues, and better appreciating the pervasiveness of uncertainty. Collaborating with non‐academic stakeholders was also particularly helpful. Most students left the course feeling more positive about the potential contribution they can make in addressing the environmental challenges that society faces.